2012
DOI: 10.1111/j.1741-2358.2012.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complete dentures on respiratory performance: spirometric evaluation

Abstract: It was observed that complete dentures may unfavourably affect spirometric values of edentulous subjects. However, current findings need to be confirmed with advanced respiratory function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Removal of the palatal part reduced the palatal bulk which in turn might have positive effect on tongue position, the associated anterior movement of the tongue's base and epiglottis may result in increased horizontal expansion of the oropharynx (1,36) . This in agreement with Piskin et al study, they found that the oropharyngeal airflow rate being unfavorably affected by the large coverage of the palate (26) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Removal of the palatal part reduced the palatal bulk which in turn might have positive effect on tongue position, the associated anterior movement of the tongue's base and epiglottis may result in increased horizontal expansion of the oropharynx (1,36) . This in agreement with Piskin et al study, they found that the oropharyngeal airflow rate being unfavorably affected by the large coverage of the palate (26) .…”
Section: Discussionsupporting
confidence: 91%
“…Several studies (21)(22)(23) found that there is a strict relationship between the upper airway and orofacial conditions. Wearing complete dentures during spirometric test had some significant effects on the respiratory performances for completely edentulous patients (24)(25)(26) . Little information was presented about the effect of palatal coverage for implant assisted overdenture on respiratory function.…”
Section: Introductionmentioning
confidence: 99%
“…[154] However, another recent study observed that FVC, FEV 1 , and PEF values obtained with dentures were slightly better than those obtained without dentures. [155] However, as the difference is small and clinically insignificant, we suggest that edentulous subjects wearing comfortable, well-fitting dentures need not remove them while performing spirometry.…”
Section: Indications and Contraindications Conducting The Test And mentioning
confidence: 98%
“…Besides, almost all dental treatment procedures have been paradoxically performed in the anterior region of oropharyngeal aperture, which facilitates respiration. Nevertheless, the effects of dental procedure type, whether invasive or noninvasive, on respiratory and cardiovascular functions have long been neglected by dentists except for a few recently published studies …”
mentioning
confidence: 99%
“…Nevertheless, the effects of dental procedure type, whether invasive or noninvasive, on respiratory and cardiovascular functions have long been neglected by dentists except for a few recently published studies. 13,14 Accurate impressions are crucial to ensure sufficient support, retention, and stability for complete dentures. 15 Despite the increased use of intraoral digital impressions (scans) in the field of prosthetic dentistry, 16 conventional impression techniques are still more reliable to obtain master casts of edentulous arches.…”
mentioning
confidence: 99%